Emotional freedom technique versus written exposure therapy versus waiting list for post-traumatic stress disorder: protocol for a randomised clinical MRI study - Hyungjun Kim; Yujin Choi; Yunna Kim; Sunyoung Choi; Young-Eun Choi; Ojin Kwon; Do-Hyung Kwon; Seung-Ho Lee; Seung-Hun Cho (BMJ Open, 2023)
Introduction The emotional freedom technique (EFT) is an acupuncture-based psychotherapy that combines tapping on acupoints with cognitive reframing. EFT has been previously shown to have potential for treating post-traumatic stress disorder (PTSD). However, further clinical evidence and underlying mechanisms of EFT are yet to be fully explored. This proposed clinical trial aims to examine the effect of EFT on patients with PTSD compared with the waitlist (WL) and active controls.Methods and analysis This study was designed as a randomised, assessor-blinded, three-arm clinical MRI study. A total of 120 eligible patients with PTSD will be recruited and randomised into EFT, written exposure therapy (WET) or WL groups. EFT and WET will be applied once a week for 5 weeks. For patients in the WL group, EFT will be performed after 12 weeks. PTSD symptoms, depression, anxiety, somatic symptoms and quality of life will be evaluated. Assessments will be conducted at baseline (week 0), post-treatment (week 6) and follow-up (week 12). Structural and functional brain images and recording videos of facial expressions to emotional stimuli will be obtained before and after treatment. Sixty participants without lifetime traumatic experiences will be enrolled as healthy controls. The primary objective of the study is to compare the change from baseline in the Clinician-Administered PTSD Scale after treatment (week 6) between EFT and WL groups and between EFT and WET groups.Ethics and dissemination Ethical approval was obtained from the Institutional Review Board of the Kyung Hee University Korean Medicine Hospital. The research findings will be shared at national and international conferences and will be published in peer-reviewed journals.Trial registration number Clinical Research Information Service KCT0007360 https://cris.nih.go.kr/cris/search/detailSearch.do/21974.